Rapid prototyping process using metal directly - Ribeiro, A. Fernando (1996)
Rapid Prototyping emerged in the USA in the late 80’s and it made the whole industry rethink their way of making prototypes. Several new different process have emerged since then and these vary in materials, times, prices, finishing quality, etc. However, not many have achieved acceptable results with using 100% pure metal. Some heavy industry want prototypes made with metal in order to assess not only the shape of the prototype but also its hardness conditions and functionality of the component in real situations. This technique is still under development at several different places and although some research have been done recently the results are not yet as desired. In the last couple of years a Rapid Prototyping process involving direct deposition of metal had been under development (as a PhD research) at Cranfield University. The process entails the use of a Gas Metal Arc fusion welding robot which deposits successive layers of metal in such way that it forms a 3D solid component. A solid model is first drawn using a CAD system, then data indicating the kind of layers and dimension is incorporated and the solid is automatically sliced. This slicing routine also generates reports on the welding time and conditions for the production of the component and automatically generates the robot program. Depending on the complexity of the component, the time from drawing the component to being ready to press the robot start button to make the component can take less than a couple of hours. Several test components were produced with good characteristics and perfectly acceptable surface finishing. This paper describes the process and shows some samples.